Modeling CMAQ dry deposition treatment over the western Pacific: a distinct characteristic of mineral dust and anthropogenic aerosols - S. S.-K. Kong; J. S. Fu; N.-H. Lin; N.-H. Lin; G.-R. Sheu; G.-R. Sheu; W.-S. Huang (Atmospheric Chemistry and Physics)
Dry deposition plays a vital role in the aerosol removal process from the atmosphere. However, the chemical transport model (CTM) is sensitive to the dry deposition parameterization but remains uncertain due to limited measurements of particle deposition. By utilizing the Community Multiscale Air Quality (CMAQ) version 5.4 with the refined dust emission treatment, the East Asian dust (EAD) simulation during January 2023 and spring 2021 was constructed to evaluate the performance of dry deposition parameterizations, namely S22, E20, and P22. The results showed that the dry deposition parameterization could significantly impact the CMAQ dust concentration in the air. By implementing the E20 dry deposition scheme, the CMAQ simulation performance of the surface PM10 has been considerably improved, with a normalized mean bias (NMB) of −41.9 %, as compared to that from S22 (−47.01 %) and P22 (−53.90 %). The modeled PM10 pattern by E20 at the upper level (700 hPa) was mostly consistent with the observed PM10 at the Lulin Atmospheric Background Station (LABS; 23.47° N, 120.87° E; 2862 m a.s.l.), which is a typical background site in the western Pacific, particularly in capturing the peak value. The correlations (R) at high altitudes were well represented for E20 by 0.55, as compared to S22 (0.54) and P22 (0.46). Moreover, E20 improved the simulated PM10 concentrations and aerosol optical depth (AOD) values over the Asian continent during the multiple dust episodes in spring 2021, by an NMB of −25.43 % and −26.19 %, respectively. The noticeable reduction of the coarse-mode particle deposition velocity (Vd) was responsible for reducing the PM10 simulation underestimation. On 22–31 January 2023, the in situ measurement of the upper level observed the possibility of natural dust and anthropogenic aerosol. This is consistent with the CMAQ, which shows that both aerosol types displayed a clear “long dust–black carbon belt” along 15° N. It is revealed that an increase in surface resistivity (Rb) leads to a significant increase in dust mass concentration but a minor increase in black carbon (BC). We propose implementing the E20 dry deposition approach, particularly in PM10 simulation, to narrow the uncertainty of the CMAQ dust emission treatment.